Intensity of climacteric syndrome in women with type 2 diabetes mellitus - Ling N. Feng, Kiran T. Varma (Open Journal of Physicians and Surgeons, 2024)
"The study aimed to investigate the intensity of climacteric syndrome in women diagnosed with type 2 diabetes mellitus. By examining the severity of climacteric symptoms such as hot flashes, mood disturbances, and sleep disturbances in women with diabetes, the research seeks to understand the potential impact of diabetes on menopausal symptoms. Understanding the interplay between climacteric syndrome and diabetes in women is crucial for optimizing management strategies, improving quality of life, and addressing the unique healthcare needs of this population. Findings from this study may contribute to a more comprehensive approach to care for women with type 2 diabetes mellitus during the menopausal transition. "